(untitled) (International Journal of Environmental Sciences, 2025)
Consumption is commonly the biggest GDP component. Especially in US while the evidence confirmed that marginal propensity to devour or MPC (ratio of exchange in intake and exchange in income) changed into regular on a long time basis and unstable in quick time period, main motives popped up. The study is naturally expected to project the prevailing socio economic conditions and the consumption pattern of women teacher in the study area. The problems of women teachers are varied in nature and they are expected to possess peculiar consumer behaviour. They are socially, economically, culturally and politically different from each other. The overall objective of the study is to analyze the consumption pattern of teacher’s in Thoothukudi Down. The study has a few limitations of time and resources. This study is limited to Thoothukudi Down. The study concentrates only on consumption pattern in the women teacher in Higher Secondary School. The other sectors like Agriculture, industry and transport are not included in the present study. The study has showed the important factors namely, annual income per household and family size of the respective households that influence the consumption in a rural economic system.